Strategi Penelitian yang Efektif Dimasa Pandemi Covid-19 - Hendi Prihanto; Nirwan Mulyatno; Islamiah Kamil (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The Covid 19 pandemic, which is an epidemic for the world, has a significant effect not only on the industrial sector, the economy, but also on the education sector. With the limited communication and learning media that existed at the beginning of the pandemic, it created a series of problems that had an impact on the quality and timeliness of study completion, not only at the undergraduate level but also at the masters and doctoral levels who experience delays due to not comprehensively understanding the strategy of writing scientific papers correctly. This activity is carried out with the aim of helping all parties, especially students who are in the process of preparing their final project. The results of the activities have a positive influence in helping students understand the writing of the final project. The results of the activity have a positive influence in helping students understand the writing of the final project, as evidenced by the enthusiasm and interest of the participants so that this kind of activity can be carried out on an ongoing basis and held again at another time.